Arquiteturas de redes de microcanais para resfriamento de chips eletrônicos - Souza, Alan Lugarini (2016)
The present work introduces microchannel nets architectures development and analysis for heat dissipation purposes. The net configurations are geometrically characterized by multiple flow ramifications and changes in length and hydraulic diameter scales through each ramification level. The current technological state has allowed manufacturing and experimentation of microchannel nets, however, it was found that architectures investigated experimentally in the past years have constant geometric parameters through their ramification levels, which is denominated fractal. In this study constructal theory is used to design net architectures with variable geometric parameters and up to three ramification levels. Some hypothesis commonly employed in macro scale analysis, for instance, fully developed flow and negligible wall-fluid thermal resistance, are reconsidered in order to comply with micro scale applications. Moreover, the architectures design is elaborated for a chip with fixed size and shape. As a result, It was verified that constructal nets allow a significant pressure drop decrease with respect to fractal nets with same ramification levels. It was demonstrated that the bifurcated net with diameter ratio according to Hess-Murray law is not appropriated for heat dissipation in miniaturized devices. Thermal resistance versus pumping power curves are shown in order to evidence the notorious superiority of constructal nets compared to fractal.